2017
DOI: 10.1186/s12866-017-1085-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis during of spore germination of Moniliophthora perniciosa, the causal agent of witches’ broom disease in cacao

Abstract: Background Moniliophthora perniciosa is a phytopathogenic fungus responsible for witches’ broom disease of cacao trees (Theobroma cacao L.). Understanding the molecular events during germination of the pathogen may enable the development of strategies for disease control in these economically important plants. In this study, we determined a comparative proteomic profile of M. perniciosa basidiospores during germination by two-dimensional SDS-PAGE and mass spectrometry.ResultsA total of 316 proteins were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The two-dimensional electrophoresis (2D-PAGE) followed by mass spectrometry was already used in studies involving M. perniciosa , such as the proteomic analyses of in vitro basidiospores germination [24], protein networks of basidiospores [25] and evaluation of M. perniciosa isolates differing in virulence on cacao seedlings [26]. Similarly, cacao proteomic studies such as protocol optimization to protein extraction [27], somatic and zygotic embryogenesis evaluation [28], seeds development and fruit ripening [29] and phylloplane protein identification in different genotypes of cacao [30] were also carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The two-dimensional electrophoresis (2D-PAGE) followed by mass spectrometry was already used in studies involving M. perniciosa , such as the proteomic analyses of in vitro basidiospores germination [24], protein networks of basidiospores [25] and evaluation of M. perniciosa isolates differing in virulence on cacao seedlings [26]. Similarly, cacao proteomic studies such as protocol optimization to protein extraction [27], somatic and zygotic embryogenesis evaluation [28], seeds development and fruit ripening [29] and phylloplane protein identification in different genotypes of cacao [30] were also carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several other studies have been published analyzing how biotrophy is maintained for so long in M. perniciosa , what the molecular mechanisms involved in the necrotrophic phase are, and the participation of hosts in signaling the end of these fungal phases [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mappa et al [ 36 ] assessed the ratio of Bacillus atrophaeus spores and vegetative cells by shotgun proteomics and identified 602 proteins. The number of proteins identified in other proteomic studies of the spores included 319 in Moniliophthora perniciosa , 118 in Botrytis cinerea spores and 148 conidial surface proteins in Aspergillus fumigatus [ 20 , 37 , 38 ]. Thus, the present study has identified a comparable number of proteins from the resting spores of S. subterranea .…”
Section: Resultsmentioning
confidence: 99%